Rhodium(III)-Catalyzed Intramolecular Benzylic C(sp3)–H Amidation for the Synthesis of Isoindolinones - Yang, Darun; Xu, Hongyan; Huang, Decai; Zhao, Huaiqing (Synthesis, 2022)
The synthesis of N-unprotected isoindolinones via rhodium(III)-catalyzed intramolecular C(sp3)–H amidation of various 2-methyl-N-substituted benzamides is developed. This protocol employs a free amino acid l-alanine as a ligand, which could significantly increase the reactivity of rhodium catalyst.
Keywords: rhodium(III) catalyst; C(sp3)–H amidation; isoindolinones; N-substituted benzamides; synthetic methods